Tomkins and Sedgwick: commentary - Marilyn Charles (Universidade Estadual de Campinas, 2011)
In contrast to trends in pedagogy and in critical theory, Alcorn & Massé bring affect to the forefront in their considerations of factors that facilitate and inhibit learning in the classroom. Using Tomkins' affect theory and Sedgwick's reading of Tomkins to focus their discussions, each highlights ways in which affect enters the classroom. They also invite us to consider some of the perils of failing to recognize ways in which affect does have an impact on ideas, learning, and even meaning itself.